METHODICAL APPROACHES TO ANALYSIS AND EVALUATION OF INNOVATION POTENTIAL OF AGRICULTURAL ENTERPRISES - KOTVYTSKA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is dedicated to the investigation of theoretical and methodological approaches to defining the innovation potential of agricultural enterprises in the agricultural sector of the economy, as well as substantiating the relevance of assessing the level of innovative development of agricultural enterprises. The article systematizes and summarizes the existing experience of methods and approaches to assessing the innovation potential of agricultural enterprises, highlights their key characteristics, and provides examples of calculation mechanisms. The advantages and disadvantages of various methods and approaches are identified. For example, a comprehensive approach that includes several indicators: innovation competencies, innovation capabilities, resources, and projects; consideration of various aspects of innovation: the method includes the assessment of various aspects of innovation potential, such as employee competencies, resource availability, ability for innovation activities, and innovative projects; adaptability: the method can be adapted to the specific needs of assessing the innovation potential of enterprises of different sizes and specificities in the agri-food sector. Among the disadvantages, we can mention subjectivity, as the assessment of competencies, capabilities, and resources can be based on the opinions and thoughts of experts; lack of a unified methodology: different methods and approaches may be used in the research, which can lead to discrepancies in the results of assessment and comparison of different enterprises; limitations of data: the assessment is based on available data, which can be limited or incomplete, and the absence of certain information may affect the accuracy of the assessment; dynamics of changes: it can be complex due to the dynamics of changes in the business environment and the speed of innovation development; contextuality: the assessment may depend on various factors, such as regional peculiarities, market conditions, competitiveness, and others. Based on this research, an improved method for evaluating the innovation potential of agri-food sector enterprises is proposed.
Keywords: innovative potential; innovation activity; agro-food sector; integrated indicator; system; criteria